Implications of land policies for rural-urban linkages and rural transformation in Ethiopia - Zewdu, Getnet Alemu; Malek, Mehrab (International Food Policy Research Institute, 2010)
In this discussion paper, we explore the policy environment related to rural-urban linkages and migration in Ethiopia, and analyze how the policies are impacting rural transformation. Section 2 describes conceptual issues and the theoretical framework that establishes the connection between RULs, rural-urban migration, and rural transformation. Section 3 outlines the policy landscape pertaining specifically to land and labor in Ethiopia, and analyzes the impact these policies have on migration behavior and rural transformation. Section 4 presents an analytic description of the macro development policy scene in Ethiopia, and critiques its role in fostering rural transformation. It also presents some key recommendations that address the shortcomings of current policies, and stimulate discussion of future policy reforms. Section 5 concludes the discussion.